Traducción de la poesía parnasiana en dos revistas de El Salvador. Análisis formal de las versiones de algunos poemas de Leconte de Lisle y José María de Heredia - Jiménez-Cervantes Arnao, Mª del Mar (Anales de Filología Francesa, 2010)
In the early years of the 20th century, at the height of Modernism, journals allow the diffusion and exchange of texts and literary movements. In the present paper we are analysing French texts published in two important journals from El Salvador. Furthermore, we are studying formal aspects in translations of Leconte de Lisle’s and Jose Maria de Heredia’s poems published in these two journals.